THE EFFECT OF COMPETENCE AND UTILIZATION OF INFORMATION TECHNOLOGY ON TAX AUDITOR PERFORMANCE WITH MOTIVATION AS VARIABLE OF MODERATION - Soraya Khairani; Vince Ratnawati; Andreas Andreas (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2021)
This study has several objectives, first to analyze the effect of competence and utilization of information technology on the performance of tax auditors. Second, analyze the influence of  competence and utilization of information technology of tax auditors which is moderated by motivation. The population of this research are 166 tax auditors in the Riau Directorate General Regional Office environment as many as 153 people and the sampling method is saturated samples. Data processed is primary data obtained by processing questionnaire data.  Data processed is primary data obtained by processing questionnaire data and were analyzed with the help of the Smart PLS Version 3.2.8  program.  The  results  of  the  study  prove  that  competence  and  utilization  of information technology has significantly affect to performance of the tax auditors. The last,  motivation  moderates  the  effect  of  competence  and  utilization  of  information technology to the performance of tax auditors.